Cultural adaptation and validation of the Italian version of the current relationship interview - Velotti, Patrizia; Rogier, Guyonne; Castellano, Rosetta; Glielmo, Eleonora; Alajmo, Valentina; Zavattini, Giulio Cesare (Frontiers in Psychology, 2023)
The study of romantic relationships is based on attachment theory and the Current Relationship Interview (CRI) is a powerful tool that allows the optimal investigation of attachment representations towards romantic partners. However, evidence in this field is still unsatisfactory and further research is needed. This study aims to examine the associations between the adult attachment to partner, the style of conflict resolution, and dyadic adjustment.We administrated the Italian version of the CRI, the Dyadic Adjustment Scale (DAS), and the Rahim Organizational Conflict Inventory questionnaire -Section II (ROCI II) -to a sample of 100 heterosexual couples.Results: Individuals with preoccupied attachment reported lower levels of dyadic adjustment and men, but not women, with preoccupied attachment reported lower levels of dyadic cohesion. Levels of dyadic adjustment reported by women/men did not vary according to their attachment types.Levels of dyadic adjustment reported by couples and by women did not vary according to the matching status of attachment types between partners. However, men in romantic relationship characterized by a mismatch between attachment types reported higher levels of consensus compared to their counterparts.The Italian version of the CRI proves an useful tool to investigate processes underlying romantic relationships. The role of current attachment in these processes appears to be highly complex and its investigation might be impacted by methodological issues, calling for additional studies.